Renal Tubule Angiotensin II Type 1 Receptor–Associated Protein Promotes Natriuresis and Inhibits Salt‐Sensitive Blood Pressure Elevation. Issue 3 (19th March 2015) - Wakui, Hiromichi; Uneda, Kazushi; Tamura, Kouichi; Ohsawa, Masato; Azushima, Kengo; Kobayashi, Ryu; Ohki, Kohji; Dejima, Toru; Kanaoka, Tomohiko; Tsurumi‐Ikeya, Yuko; Matsuda, Miyuki; Haruhara, Kotaro; et al.
Abstract : Background: Angiotensin II type 1 receptor (AT1R)–associated protein (ATRAP; Agtrap gene) promotes AT1R internalization along with suppression of pathological AT1R activation. In this study, we examined whether enhancement of ATRAP in the renal distal tubules affects sodium handling and blood pressure regulation in response to high salt (HS) loading, using ATRAP transgenic mice on a salt‐sensitive C57BL/6J background. Methods and Results: Renal ATRAP transgenic (rATRAP‐Tg) mice, which exhibit renal tubule–dominant ATRAP enhancement, and their wild‐type littermate C57BL/6J mice on a normal salt diet (0.3% NaCl) at baseline were subjected to dietary HS loading (4% NaCl) for 7 days. In rATRAP‐Tg mice, the dietary HS loading–mediated blood pressure elevation was suppressed compared with wild‐type mice, despite similar baseline blood pressure. Although renal angiotensin II level was comparable in rATRAP‐Tg and wild‐type mice with and without HS loading, urinary sodium excretion in response to HS loading was significantly enhanced in the rATRAP‐Tg mice. In addition, functional transport activity of the amiloride‐sensitive epithelial Na + channel was significantly decreased under saline volume–expanded conditions in rATRAP‐Tg mice compared with wild‐type mice, without any evident change in epithelial Na + channel protein expression. Plasma membrane AT1R expression in the kidney of rATRAP‐Tg mice was decreased compared with wild‐type mice. Conclusions: These results demonstrated that distal tubule–dominant enhancement of ATRAP inhibits pathological renal sodium reabsorption and blood pressure elevation in response to HS loading. The findings suggest that ATRAP‐mediated modulation of sodium handling in renal distal tubules could be a target of interest in salt‐sensitive blood pressure regulation.